An evaluation for the Therapeutic Learning Centre: A child inpatient and day-patient psychiatric unit in Cape Town, South Africa - Nicholson, Lee (Organisational Psychology, 2020)
There are value and importance for inpatient and day-patient psychiatric units, particularly for children and adolescents. These facilities, which are scarcely established in South Africa, offer multidisciplinary and multifaceted treatment to persons experiencing varying symptoms and conditions of mental illness. This dissertation presents the findings of an implementation evaluation conducted for the Therapeutic Learning Centre (TLC), a child inpatient psychiatric unit in Rondebosch, Cape Town. The evaluation aimed to compare the TLC’s service and programme implementation with international standards. The Quality Network for Inpatient Child and Adolescent Mental Health Service (QNIC) checklist was used to assess the TLC on seven focused categories of service and implementation quality. Data were provided from selected TLC team members, which included mental health practitioners from various fields (e.g., psychology, psychiatry and social work to name a few). Overall, the programme established within the TLC was found to be implemented with fair fidelity when compared to the international unit standards. Most unit standards required and expected to be carried out by an inpatient unit were found to be satisfied by the TLC. There are, however, key aspects of the unit’s environment and facilities, staffing and training, care and treatment, and clinical governance that were highlighted as needing improvement. While the research yielded mostly positive results, the evaluator was able to make several recommendations to the TLC stakeholders. This evaluation contributes to limited research and implementation evaluations within the context of child inpatient psychiatric units. Furthermore, the findings are intended to support the promotion of quality psychiatric and behavioural treatment and mental health service policy in these units within South Africa.